Implementasi Constrained Application Protocol (CoAP) Pada Semantic IoT Web Service - Made Rezananda Putra; Eko Sakti Pramukantoro; Fariz Andri Bakhtiar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Heterogeneous communication protocols in internet of things lead to problems of interoperability, in particular the syntactical interoperability. In previous research has developed semantic IoT web service that can receive data from the sensors node via HTTP. However, the use of HTTP is not enough to receive data from the sensors node with diverse communication protocols. These problems are also compounded by the existence of a sensor node has limited or resource-constrained. One of the solutions of these problems is the addition of communication protocol on semantic IoT web service to connect with a resource-constrained sensor node. Constrained Application Protocol (CoAP) is a communications protocol that is capable of handling the problems of resource-constrained. CoAP designed to use minimal resources, making it suitable to be implemented on the environment the IoT has limitations. Therefore, in this study will be added CoAP as the protocol communications on semantic IoT web service. In terms of functional test results indicate semantic IoT web service is able to accept JSON-shaped data, images and video via communication protocols CoAP. The addition of the CoAP on semantic IoT web service is also capable of handling the problems of interoperability, in particular the syntactical interoperability by providing communication protocol via HTTP and CoAP.